Microeconometric Analysis of Individual and Institutional Determinants of Education and Occupational Choice - Natalie Obergruber (ifo Institut – Leibniz-Institut für Wirtschaftsforschung an der Universität München, 2018)
This study analyses which individual and institutional factors (causally) influence individuals in their educational career and in their choice for an occupation. Chapter 2 explores consequences of parental separation for cognitive skill development of children. In the year before parental separation occurs children are negatively affected in their cognitive skill development. Chapter 3 investigates the consequences of an institutional reform in the German school system which awards high track school drop outs with lower track school degrees if they accomplished 9th grade. After the reform students are less likely to switch between schools and tracks and surprisingly are more likely to successfully finish the high-track school and enter university. Chapter 4 predicts the choice of math-intensive occupations by school grades. School grades are affected by students' ability and tastes and may furthermore contain pure signals of achievement (based on rank in class). We find that the strong association between grades and math intensity of occupations is completely explained by individuals' differences in tastes. Chapter 5 shows that occupational choice is influenced by the distribution of land, a store of wealth in an agricultural society. We find that areas with more equally distributed land started to industrialize earlier particularly in innovative manufacturing.
Keywords: I21; I24; I28; J12; J13; J24; N13; N33; O33; O47; 330; difference-in-differences; economic inequality; industrialization; panel data; NEPS